Optimal Beliefs, Asset Prices, and the Preference for Skewed Returns - Brunnermeier, Markus K; Gollier, Christian; Parker, Jonathan A (American Economic Review, 2007)
Optimal Beliefs, Asset Prices, and the Preference for Skewed Returns by Markus K. Brunnermeier, Christian Gollier and Jonathan A. Parker. Published in volume 97, issue 2, pages 159-165 of American Economic Review, May 2007